Digestible Lysine Requirements of Male Turkeys During the 12 to 18 Week Period - Baker, K.; Firman, J.D.; Blair, E.; Brown, J.; Moore, D. (International Journal of Poultry Science, 2003)
Two floor pen trials were conducted using turkey toms in order to determine the digestible lysine requirement for the 72 to 83 and 84 to 95 day feeding periods. Prior to the studies, birds were fed a typical corn, soybean meal (SBM) and porkmeal based diet. At the beginning of each trial, birds were weighed and sorted into 48 floor pens in a curtain-sided building. Dietary treatments for the first experiment included eight levels of digestible lysine ranging from 0.54 to 0.75% and from 0.44 to 0.65% in the second experiment. A positive control treatment was added at the expense of three replicates of the highest lysine level. The lysine deficient basal diet was corn, SBM, and porkmeal based with intact crude protein levels of 14.3% in the first experiment and 13.2% in the second experiment. The positive control diet was also corn, SBM and pork meal based and was formulated on a total AA basis to meet or exceed nutrient requirements set by the NRC (1994). Lysine-HCL (98.5%) was used for the titration and glutamic acid was titrated inversely to keep nitrogen levels similar. The experiments were set up as randomized complete blocks and the trial periods lasted for eleven days. Segmented regression analysis determined the digestible lysine requirement for the 72 to 83 day period to be 0.68 and 0.67% for growth and feed conversion, respectively. For the 84 to 95 day period, the digestible lysine requirement was determined to be 0.53% for optimum bodyweight gain and 0.54% for feed conversion.